Ett svåröverblickbart skeende – en analys av utformningen av gärningsbeskrivningar i mål om krigsförbrytelser - Wetterberg,Johanna (2023)
War crime cases are a relatively new phenomenon in Swedish courts and often serve as a typical example of what can be considered major criminal cases. Often the proceedings are preceded by lengthy preliminary investigations due to crimes being complicated and hard to investigate, resulting in significant amounts of trial material. Consequently, these cases tie up the resources of the judiciary and the parties involved for a long time. Given that the increase in large criminal cases places new requirements on the court's proceedings, amendments have been made to the Code of Judicial Procedure (sv: rättegångsbalken) to achieve greater efficiency and legal certainty in the trial procedure. In 2022, an explicit regulation of the court's responsibility for the conduct of the proceedings during preparatory proceedings was introduced, requiring that the court at an early stage of the process clarifies the prosecutor's statement of the criminal act. The purpose of this paper is to examine and discuss whether the criminal procedural rules concerning the formulation of the statement of the criminal act as charged are structured and applied to meet the new challenges posed by the handling of major criminal cases. The study is based on war crime cases. The case study shows that there are deficiencies in the statements of the criminal acts in war crime cases. This is partly due to the fact that the sequence of events is presented at a general level and consists of the actions of several different perpetrators. The statements of the criminal acts do not refer to a specific number of individual acts that are concretized or specified in more detail in time and space. The clarity of the descriptions of the acts is affected by the nature and structure of the overall sequence of events and the degree of precision in the given indications of time and place. Herbert L. Packer’s Crime Control Model and Due Process Model are used to analyse whether the measures that the court may take if the statement of the criminal act is deficient can ensure an effective crime control and a fair procedure. The investigation suggests that direction of proceedings is an appropriate measure, especially if conducted during preparatory proceedings. Furthermore, the investigation proposes a provision in the Code of Judical Procedure whereby the court can order the prosecutor to supplement the statement of the criminal act if there are deficiencies in the statement of the criminal act. It is also proposed to introduce a new provision in the Code of Judical Procedure whereby the court may dismiss an action if the order to supplement does not result in an acceptable statement of the criminal act. This is expected to contribute to a criminal procedural framework that can better ensure an effective crime control and a fair procedure. Lastly, the investigation raises the need for further research concerning the formulation of statements of the criminal act in other types of cases, as this can provide a basis for further discussion of how the rules on statements of the criminal act should be formulated and applied.
Keywords: straffrätt